Characterization of a novel bile acid-based delivery platform for microencapsulated pancreatic ß-cells. - Mooranian, Armin; Negrulj, R.; Arfuso, Frank; Al-Salami, Hani (2014)
Introduction: In a recent study, we confirmed good chemical and physical compatibility of microencapsulated pancreatic β-cells using a novel formulation of low viscosity sodium alginate (LVSA), Poly-L-Ornithine (PLO), and the tertiary bile acid, ursodeoxycholic acid (UDCA). This study aimed to investigate the effect of UDCA on the morphology, swelling, stability, and size of these new microcapsules. It also aimed to evaluate cell viability in the microcapsules following UDCA addition. Materials and methods: Microencapsulation was carried out using a Büchi-based system. Two (LVSA-PLO, control and LVSA-PLO-UDCA, test) pancreatic β-cells microcapsules were prepared at a constant ratio of 10:1:3, respectively. The microcapsules’ morphology, cell viability, swelling characteristics, stability, mechanical strength, Zeta potential, and size analysis were examined. The cell contents in each microcapsule and the microencapsulation efficiency were also examined. Results: The addition of UDCA did not affect the microcapsules’ morphology, stability, size, or the microencapsulation efficiency. However, UDCA enhanced cell viability in the microcapsules 24 h after microencapsulation (p < 0.01), reduced swelling (p < 0.05), reduced Zeta potential (− 73 ± 2 to − 54 ± 2 mV, p < 0.01), and increased mechanical strength of the microcapsules (p < 0.05) at the end of the 24-h experimental period. Discussion and conclusion: UDCA increased β-cell viability in the microcapsules without affecting the microcapsules’ size, morphology, or stability. It also increased the microcapsules’ resistance to swelling and optimized their mechanical strength. Our findings suggest potential benefits of the bile acid UDCA in β-cell microencapsulation.